Anthropometric measurements and assessment of functional status - Hliadia, S. O.; Yushko, O. V.; Boreiko, N. Y.; Bilous, O. V. (My University, 2023)
Methodical recommendations have been prepared for full-time students of all specialties NTU «KhPI» (main medical group, special medical group) for transferring the educational process to a distance form of education. Students are offered the organization of self-monitoring of their physical condition, mastering the anthropometry method by studying their own body dimensions, enriching the necessary theoretical knowledge, conducting a functional test (orthostatic test), the ability to analyze the obtained results. Evaluation criteria for practical work have been established «Anthropometric measurements and assessment of functional status». A sample structure of practical work is provided.
Keywords: methodological recommendations; general terms; organization of practical work; evaluation criteria for practical work; requirements for registration of practical work; structure of practical work